Proself or Prosocial? The Indonesian Academics Motive to Commercializing University Research - Nurul Safitri; Martani Huseini; Retno Kusumastuti (International Journal of Technology)
Commercialization represents an important way for academics to contribute to economy and society.This study aimed to investigate the motivation of Indonesian academics to commercialize their research findings. A model linking proself and prosocial with scientific entrepreneurship was used to assess the motivation of Indonesian academics to commercialize their research finding. A quantitative method with survey design was used, and the data were collected through an online self-administered questionnaire. Furthermore, the respondents were academics from ten universities with legal entity status (PTNBH) in Indonesia with a scientific backgrounds in engineering, science, and health. Descriptive analysis with central tendency was carried out using SPSS 24. Meanwhile, to investigate the relationships between the variables, the inferential statistical analysis using SEM PLS was carried out using the Smart PLS 3. The results showed that the motivation of Indonesian academics to commercialize university research was influenced by proself, but the effect was restricted to the intention to commercialize and did not directly affect research commercialization. Meanwhile, prosocial motivation had no significant impact on the intention to commercialize. This showed that Indonesian academics had a strong desire to engage in research commercialization, but only few had been successful through licensing or creating startups. The majority had a hybrid and entrepreneurial orientation toward university-industry links.